PENGAMANAN DATA DENGAN ALGORITMA RSA (Rivest Shamir Adleman), LZW (Lempel Ziv Welch) DAN EOF (End Of File) PADA DIVISI MARKETING RS KPJ MEDIKA BSD - Silvester Rian Ananta; Imelda Imelda (Universitas Budi Luhur, 2016)
KPJ Medika Hospital BSD is a private general hospital in Bumi Serpong Damai South Tangerang. At KPJ Medika Hospital BSD each computer are connected in a local network, and local networks that exist in the hospital connected to the internet, which means is connected to the WAN (Wide Area Network). The problem that arises is when there are parties who are able to break into the security of the local network and steal important data that exist on each computer. With this condition, the hospital needed a solution related to data security issues. Therefore, this paper aims to provide a solution to secure data on hospital KPJ Medika BSD. Encryption and steganography is a solution of data security. Encryption is a data security with encryption methods to the data itself. The result of this encryption will be compressed before stegangrafi process. Steganography is the insertion of data into other media such as pictures, videos, and music. But in this study, the data is only inserted into the picture. Initially the data will be encrypted using RSA. Then data result of encryption will be compressed using LZW. Then inserted into the image using the EOF. The result is data on marketing division will be stored and safely obscured by the media images, only those who are entitled only to read the data on marketing division. Thus the important data on the marketing division at the hospital KPJ Medika BSD is more secure because the data has been encrypted by RSA cryptography, compressed by LZW and obscured by steganography EOF.